Habitus, representações sociais e construção identitária dos professores de Maracanaú - Albuquerque, Lia Matos Brito de (2005)
In the last three decades, the subject of the teacher's social identity has been discussed under various theoretical focuses, not only in Brazil, but also beyond our borders. In this thesis, the theme is approached starting from the theoretical proposal that has been developed by Domingos Sobrinho (1994), which is strongly based in the epistemological approach between Pierre Bourdieu’s praxiology and the Theory of the Social Representations formulated by Serge Moscovici. It presupposes that this would make it easier to apprehend the process of construction of social identity of the investigated social group. The universe of the research is constituted by teachers of the fundamental teaching of the municipal district of Maracanaú, state of Ceará, that were active in class-room work there during at least three years, and were registered or had concluded the Course of Educational Formation promoted by UECE in that municipal district. Taking into account that the teacher's social identity is a process in permanent construction, resulting of their daily experiences and of the interferences originated from of the social context, the investigative tasks were implemented in two different stages, although they complement each other. Initially, with the objective of putting in evidence the genesis of the formation of that group’s habitus, an analysis of the family and school lives of eleven teachers who participated in the course was made, using as main sources of data: thematic memorials, semi-structured interviews and observations - inside and out of the class-room – during four school semesters. In the second stage a test of free association of words was applied to 426 teachers, seeking to apprehend the structure of the social representations of family and school – a methodological strategy considered necessary to enhance and identify certain outlines of the habitus in study, besides being in agreement with the theoretical model followed. It became evident from the results that the identity of Maracanaú’s teachers is molded and transformed into a multifaceted dynamic unit that shows successes and mistakes, certainties and doubts. For instance, besides an innovative speech seeking to reassure that teaching is a profession and not a simple vocation or mission, some discourse and attitudes are identified that point to the opposite direction, extolling the school as extension of the family, defending a parental relationship with the students, and looking at certain aspects of daily school life as “sacramental”. However, in the light of science such ambiguities and incoherences are inherent to common sense discourse, where the influences of the patterns and cultural references are present in the process of identity construction of the group, which was confirmed by the research of their social representations of family and school